IDENTIFICATION OF THE ORB WEAVING SPIDER (ARANEAE: ARANEIDAE) FAUNA OF DIR LOWER (PAKISTAN) THROUGH DNA BARCODING - M. Sajid1; M.Zahid; M. Shah; M. Rasool; I.Ullah; R. Ahmad; P. Habibullah; N. Majeed (Journal of Animal and Plant Sciences, 2021)
As a result of faunistic study on the Orb weaving spider fauna of Pakistan one genus, Gibbaranea Archer, 1951 and six species, Argiope versicolor (Doleschall, 1859), Argiope lobata(Pallas, 1772), Neoscona polyspinipes(Yin, Wang, Xie and Peng, 1990), Neoscona scylla (Karsch, 1879), Gea spinipes (C. L. Koch, 1843) and Gibbaraneaullrichi(Hahn, 1835) are recorded from Pakistan for the first time and the presence of five species are confirmed. Eriovixia excelsa (Simon, 1889) and Araneus mitificus (Simon, 1886) are recorded for the first time since 1935.COI sequences >200 bp recovered from 23 specimens were analyzed using neighbor-joining trees and Barcode Index Numbers (BINs)Nucleotide alignmentfor each species is provided with Sample id, Process id, match process id and match BIN. A map showing the local distribution of each species is provided.
Keywords: Dir Lower; Aranei; new records; distribution; taxonomy